Adventurous plot in the Ukrainian avant-garde novel (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
In the article features adventure story in the works of Mike Johansen, O. Slisarenko, Geo Shkurupii, Julian Shpola, Y. Yanovsky. The components adventure story in vanguard novel is adventure, travel, unexpected denouement work puzzles, plot, the effect of authenticity, links to images of historical events and characters.
Keywords: adventure; adventure story; plot; character; effect of surprise; mystery